Consistency of ocular coherence tomography fast macular thickness mapping in diabetic diffuse macular edema (Clinics, 2007)
OBJECTIVES: To investigate optical coherence tomography consistency on foveal thickness, foveal volume, and macular volume measurements in patients with and without diffuse diabetic macular edema. INTRODUCTION: Optical coherence tomography represents an objective technique that provides cross-sectional tomographs of retinal structure in vivo. However, it is expected that poor fixation ability, as seen in diabetic macular edema, could alter its results. Several authors have discussed the reproducibility of optical coherence tomography, but only a few have addressed the topic with respect to diabetic maculopathy. METHODS: The study recruited diabetic patients without clinically evident retinopathy (control group) and with diffuse macular edema (case group). Only one eye of each patient was evaluated. Five consecutive fast macular scans were taken using Ocular Coherence Tomography 3; the 6 mm macular map was chosen. The consistency in measurements of foveal thickness, foveal volume, and total macular volume for both groups was evaluated using the Pearson's coefficient of variation. The T-test for independent samples was used in order to compare measurements of both groups. RESULTS: Each group consisted of 20 patients. All measurements had a coefficient of variation less than 10%. The most consistent parameter for both groups was the total macular volume. DISCUSSION: Consistency in measurement is a mainstay of any test. A test is unreliable if its measurements can not be correctly repeated. We found a good index of consistency, even considering patients with an unstable gaze. CONCLUSIONS: Optical coherence tomography is a consistent method for diabetic subjects with diffuse macular edema.